An Evaluation of The Performance and Comparative Cost of Ground-mounted and Rooftop Mounted Solar Photovoltaic Systems - Leighton, Michael (Energy Research Centre, 2021)
In South Africa, there is an increasing interest in installing rooftop mounted solar photovoltaic systems. However, financing the photovoltaic systems causes most interest to be abandoned, largely due to the cost required to replace a building's asbestos roof. An alternative solution to replacing an asbestos roof is to install a ground-mounted photovoltaic system, which is more costly compared to a rooftop mounted system. This study aims to determine if a ground-mounted or a rooftop mounted solar photovoltaic system is the most financially feasible solar photovoltaic configuration. In this study three photovoltaic systems were analysed, all of which are installed in Atlantis, Western Cape (WC). Since all three systems are in the same area, they are all exposed to the same metrological conditions, allowing for identical energy generation potential. Two of the photovoltaic systems are ground-mounted systems located respectfully at the South African Renewable Energy Incubator (SAREBI) and at Stripform Packaging. The third system is a rooftop mounted system located at SA Tyre Recyclers. The photovoltaic system at SAREBI is a 9.75 kWp system consisting of 30 Canadian Solar CS6U-325P modules, one Schneider Electric 20 kW inverter, a tilt angle of 15° and an azimuth angle of -19°. The photovoltaic system at SA Tyre Recyclers is a 231 kWp system consisting of 700 JA Solar JAP72S-01-330-SC modules, 7 SolarEdge 27.6 kW inverters, a tilt angle of 13° and an azimuth angle of 22°. The photovoltaic system at Stripform Packaging is a 20.1 kWp system consisting of 60 Canadian Solar CS6U-335P modules, one SMA 20 kW inverter, a tilt angle of 15° and an azimuth angle of 46°. To achieve the aim of this study, the performance of each of the solar photovoltaic systems was examined, by comparing their annual specific yield. After which the technical aspects and differences of each of the photovoltaic systems were explored, to illustrate how each of the systems differ technically and how each system can be improved. Finally, the comparative cost of each of the solar photovoltaic systems was examined by analysing the levelized cost of energy (LCOE) and the payback period for each of the photovoltaic systems. The results demonstrated that from an annual specific yield perspective, the ground-mounted configuration was the best performing, whilst from a financial perspective, the rooftop mounted configuration had the lowest levelized cost of energy (LCOE) and payback period. However, installing a ground-mounted system is more financially feasible than replacing an asbestos roof and then installing a rooftop mounted system. In conclusion, by fully understanding the performance, payback period and levelized cost of energy, a clear understanding of potential risk can be determined, thus making the installation of photovoltaic systems more appealing for financiers. It is recommended that this study be repeated in a manner in which each of the photovoltaic system configurations are constructed consisting of all the same photovoltaic components, measuring equipment, tilt and azimuth angles. All of which would result in two identical photovoltaic systems where one is installed on a rooftop and the other installed on the ground. Once the two photovoltaic system configurations are equal in all aspects, an accurate comparison to determine which configuration is the most optimal performer and which is the most financially viable will be possible.